Shared humanity, awareness of socio-economic privilege, and classism during the pandemic as predictors of supporting equal socio-economic policies - Uluğ, Özden Melis (Curr Psychol, 2021)
The coronavirus pandemic has caused unemployment to skyrocket, exposed the longstanding inequalities in health care services and working conditions, and mainly affected the poor in different parts of the world. In the current study, we focus on social identity and social class-related factors that are critical during the pandemic to gain insights into what predicts support for policies favoring economic equality in the post-pandemic period. We argue that to the extent that individuals 1) identify with all humanity during the pandemic, 2) are aware of their socio-economic status-based privilege, 3) do not hold classist attitudes, they would support policies favoring economic equality. In Study 1, survey data from 1212 participants in Turkey were analyzed by means of hierarchical linear regression analysis. The findings showed that stronger identification with all humanity, higher awareness of socio-economic status-based privilege, and less endorsement of classist attitudes predict more support for socio-economic equality policies in the post-pandemic period, after controlling for socio-demographic and socio-political characteristics of participants. Study 2 (N = 212) replicated the findings in a different context, namely the U.S. Our findings extend previous studies by showing the importance of a global identity, such as shared human identity, in the ongoing and potentially in the aftermath of the pandemic. In addition, our findings highlight the joint contributions of socio-economic factors such as classist attitudes and awareness of class-based privilege to the support for socio-economic policies.